Synthesis of Polydopamine-Like Nanocapsules via Removal of a Sacrificial Mesoporous Silica Template with Water - Nador, Fabiana Gabriela (2017)
Hollow polymeric polydopamine (PDA) micro-/nanocapsules have been obtained through a very simple, mild, and straightforward method that involves coating of silica mesoporous nanoparticles through an ammonia-triggered polymerization of PDA and the posterior removal of the sacrificial template simply by dispersion in water, without the need of any harsh chemical reagent, either in the presence or absence of active principles, from doxorubicin to iron oxide nanoparticles. To demonstrate the potential of the nanocapsules obtained with this new approach, they have been successfully used as nanocarriers for drug delivery.